LANAUDIÈRE HEAVEN FOR COLOMBIAN REFUGEES: THE REALITY OF WHAT IS AND THE DREAM OF WHAT COULD BE - Robichaud, Fanny; Lacharité, Carl; Montigny, Francine (LIFE: International Journal of Health and Life-Sciences, 2016)
Considering the steady increase in the arrival of refugee families, it seems essential to point out the challenges this new reality raises and to explore avenues that would result in a positive experience for families. The authors suggest challenging our perceptions of the refugees’ experience by giving a voice to these families and daring to consider them as experts in their own experience. Appreciative inquiry was used to explore not only the challenges faced by refugee families, but also to uncover the successes and shed light on new solutions. The importance of including families in the research process and in discussions related to the development of services stands out, as well as the empowering effect of recognizing the family wisdom.